Alg 1 ch. 5.3 - functions

398 views

Published on

Published in: Education
0 Comments
0 Likes
Statistics
Notes
  • Be the first to comment

  • Be the first to like this

No Downloads
Views
Total views
398
On SlideShare
0
From Embeds
0
Number of Embeds
7
Actions
Shares
0
Downloads
2
Comments
0
Likes
0
Embeds 0
No embeds

No notes for slide

Alg 1 ch. 5.3 - functions

  1. 1. Agenda 11/8 Review functions Do Now Homework check Homework 4 p. 249 # 1 - 12 all Follow all directions Use graph paper Quiz Friday? 5.1 - 5.4
  2. 2. 5.2 RELATIONS AND FUNCTIONS 11/8 Relation a set of ordered pairs it can be expressed as: Ordered Pairs (-1, 1) (0, 2) (1, 3) (2, 4) Table x x 2 Mapping -1 1 0 2 1 3 2 4 Graph y -1 1 0 2 1 3 4
  3. 3. The Vertical Line Test Otherwise known as the stupid pencil trick! If a vertical line intersects more than one point on a graph, it is not a function. An x-value cannot have 2 different y-values.
  4. 4. Do Now RELATION: (1, 4) (-2, 3) (0, 3) (1, 2) Please show this relation in these ways: TABLE MAPPING GRAPH Is this a function? Why or why not?
  5. 5. HW CHECK
  6. 6. 22. 9 23. -16.5 24. 6 2/3 25. -5.25 26. 90 27. 28 28. 17.6 29. 67.5 30. 700 31. 105.6 km 32. 0.5 33. 8 11/12 34. 7 1/3 35. - 3 1/2 36. 8 37. 165 p. 185 # 22 - 37
  7. 7. Function Notation y = 3x - 4 f(x) = 3x - 4 } EQUIVALENT f(x) = "the f of x" - what you do to x f(x) = 4x - 1 f(2) = ? -- 4(2) -1 = 7 f(2) = 7 the value of the function when x = 2
  8. 8. PRACTICE f(x) = x + 2; f(3) = ? 5 f(x) = x3 + 4; f(2) = ? 12 g(x) = 2x - 1; g(-2) = ? -5 f(x) = -x2 + 5; f(-2) = ? 1 f(x) = x + 1; g(x) = 2x; f(g(3)) = ? 7
  9. 9. input output RULE x-values domain inputs independent variables y-values range outputs f(x)-values dependent variables
  10. 10. EQUATIONS AS FUNCTIONS When a function is written as an equation, we can make a graph. example: y = 2x + 1 1. Make a table and choose input values (x). x y (x, y)y = 2x + 1 2. Fill in table to get ordered pairs. 3. Graph ordered pairs and make a line.
  11. 11. y = x - 2 x y (x, y)y = x - 2 y = 1/3 x - 2 x y (x, y)y = 1/3 x - 2

×